Molecular bird sexing of sulphur‐crested cockatoo (Cacatua galerita) by polymerase chain reaction method - Diana Savitri; Irhamna Putri; Warih Pulung Nugrahani; Medania Purwaningrum; Aris Haryanto (Indonesian Journal of Biotechnology, 2021)
Sex identification of endangered and protected birds in captivity is very important for conservation programs. Half of the world’s bird species are monomorphic, where male and female are difficult to distinguished morphologically, including cockatoos. Sex identification using molecular bird sexing is more accurate and applicable because it directly targets the sex chromosomes. The purpose of this study was to determine the sex of Sulphur‐crested cockatoo (Cacatua galerita) by detecting differences in the intron size of the chromodomain helicase DNA‐binding 1 (CHD1) gene on the Z and W chromosomes by polymerase chain reaction (PCR) method and to compare of plucked feathers and blood samples as DNA sources for molecular bird sexing. DNA was extracted from feather and blood samples from four C. galerita. Extracted DNA was amplified on the CHD1 gene by PCR method with P2, MP, and NP primers, which were visualized using agarose gel 1.5% under UV transilluminator with a wavelength of 280 nm. The resulting PCR product was detected at 392 bp for the CHD1 Z gene segment and 297 bp for CHD1 W gene segments, where males showed a single DNA band (ZZ) and females showed a double DNA band (ZW). Four C. galerita were 100% successfully determined, consisting of one female and three males. Electrophoresis results showed DNA bands from blood samples were thicker and brighter than DNA bands from feather samples.